PERANCANGAN DESAIN MESIN VAKUM PEMISAH LIMBAH GERAM DENGAN OIL CUTTING MENGGUNAKAN AUTODESK INVENTOR : DESIGN OF VACUUM MACHINE FOR SEPARATING METAL SCRAP WASTE WITH OIL CUTTING USING AUTODESK INVENTOR - Yulia Puspa Dewi; Setiawan, Deny; Cahyono, Hiding; Mutiara Bahtiar, Ahmad Dony; Riswan Eko Wahyu Susanto (Jurnal Teknik Mesin, 2023)
Metal scrap waste mixed with oil cutting can reduce the quality of the oil cutting itself, so it cannot be used directly. Meanwhile, the waste that is mixed with oil cannot be processed directly such as recycling / remelting. Cutting oil as a cooling material for the cutting process, so from here the recycle of cutting oil is needed, so a tool/machine is needed to separate the waste from the oil cutting. The research method used is design research which consists of planning machine elements and making machine designs. In the planning of machine elements, more emphasis is placed on the impler blade of the vacuum separator while the drawing uses Autodesk Inventor. From the results of the design and design of the "vacuum separator" it is obtained that; the dimensions of the impeller are 20 mm in diameter, the impeller neck is 28 mm in diameter, the impeller eye and the inlet side are the same diameter 92 mm, the inlet side of the impeller has an angle of 16 °, the width of the bow is 18.85 mm, while the distance between the blades (?1) is 48.17 mm, the diameter of the outgoing side of the results of the calculation is 230 mm, the angle of the outgoing side of the impeller is 25 ° and the wide side of the impeller is 7.5 mm, at the distance between the blades of the incoming side (?2) 120.42 mm. So that from the design of the machine element, the number of impellers is obtained 6 blades, with the results analyzed with a safety factor of 15 Ul.